Encephalomyocarditis virus infection in alpacas. Issue 10 (13th August 2020) - O'Connor, TW; Finlaison, DS; Manning, LK; Hazelton, MS; Spiers, ZB; Pinczowski, P; Bolin, EM; Kemsley, PD; Horadagoda, NU; Dart, AJ; Cook, RW; Kirkland, PD
Abstract : Encephalomyocarditis virus (EMCV) infection was detected by real‐time reverse transcription PCR (qRT‐PCR) in four adult alpacas ( Vicugna pacos ) from two properties on the Far North Coast of New South Wales (NSW) in April and May 2018 and in two adult alpacas from a third property on the Central Coast of NSW in October 2018. Viral RNA was detected in a range of samples, including blood, fresh body organs and mucosal swabs. EMCV was isolated from the blood and body organs of five of these alpacas. These animals displayed a range of clinical signs, including inappetence, colic, recumbency and death. Necropsy findings included multifocal to coalescing areas of myocardial pallor, pulmonary congestion and oedema, hepatic congestion and serosal effusion. Histopathological changes comprised acute, multifocal myocardial degeneration and necrosis, with mild, neutrophilic and lymphocytic inflammation (5/5 hearts) and mild, perivascular neutrophilic meningoencephalitis (1/3 brains). This is the first report of disease due to EMCV in alpacas under farm conditions, and it identifies EMCV infection as a differential diagnosis for acute disease and death in this camelid species. In addition to the samples traditionally preferred for EMCV isolation (fresh heart, brain and spleen), blood samples are also appropriate for EMCV detection by qRT‐PCR assay.